Surgical guided tissue regeneration treatment of advanced periodontal defects: a 5-year follow-up study - Christer Slotte (Blackwell Synergy, 2007)
Objectives: To study the 5-year outcome of combined use of guided tissue regeneration (GTR) barriers and bovine bone in advanced periodontal defects. Material and Methods: In each of 24 patients, one defect was surgically exposed, debrided, filled with bovine bone, and covered with a bioresorbable barrier. Re-examinations were made after 1, 3, and 5 years. Results: Average full-mouth plaque scores (FMPS) were 14.5% at baseline and 10.7%, 9.8%, and 18.9% after 1, 3, and 5 years, respectively. Mean probing pocket depth (PPD) was 10.0mm at baseline. Mean PPD reduction was 5.2mm after 1 year, 5.6mm after 3 years, and 5.3mm after 5 years. Mean gingival recession was 1.0mm after 1 year, 1.6mm after 3 years, and 1.3mm after 5 years. Mean gain in clinical attachment level (CAL) was 4.2mm at the 1-year, 4.1mm at the 3-year, and 4.3mm at the 5-year examination. Smoking significantly influenced CAL change at all re-examinations. FMPS were significantly correlated with radiographic defect depth at the 5-year examination and CAL with smoking and FMPS at the 3-year examination. Conclusion: Advanced periodontal defects can be successfully treated with the combined use of GTR barriers and bovine bone to substantially reduce PPD and achieve a stable, long-term gain of CAL.